Evaluasi Kebijakan Pengelolaan Sampah Berbasis Masyarakat di Gresik Sebagai Upaya Menuju Kabupaten Hijau - Aditya Hermansyah; Ulul Albab; Zainal Fatah; Ika Devy Pramudiana (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Community-based waste management is a strategic step toward achieving sustainable development in Gresik Regency, Indonesia. This policy aims to reduce waste volume, raise community awareness, and support the vision of a Green Regency. This study evaluates the implementation and effectiveness of community-based waste management policies using a qualitative case study approach. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed thematically to identify supporting and hindering factors influencing program success. The findings indicate that while progress has been made, significant challenges remain, including low levels of socialization, limited infrastructure, and weak inter-agency coordination. Community participation depends heavily on local leaders and facilitators, and the sustainability of institutions such as waste banks and management groups has yet to be evenly distributed. Adequate infrastructure, such as integrated waste processing facilities (TPS3R), is crucial and needs enhancement. Barriers like a lack of technical experts, cultural habits of indiscriminate waste disposal, and insufficient funding hinder the achievement of policy objectives. This evaluation underscores the necessity for increased education, institutional strengthening, and improved infrastructure to accelerate behavioral change and boost community participation. The results are expected to inform local government strategies for more effective implementation toward realizing a sustainable and environmentally friendly Gresik. An integrated and holistic approach is essential for optimizing waste management, creating a cleaner, healthier, and sustainable environment.